Identifying potential moderators for response to treatment in low back pain: A systematic review. Issue 3 (September 2015) - Gurung, Tara; Ellard, David R.; Mistry, Dipesh; Patel, Shilpa; Underwood, Martin
Abstract Background Identifying which patients with non-specific low back pain are likely to gain the greatest benefit from different treatments is an important research priority. Few studies are large enough to produce data on sub-group effects from different treatments. Data from existing large studies may help identify potential moderators to use in future individual patient data meta-analyses. Objective To systematically review papers of therapist delivered interventions for low back pain to identify potential moderators to inform an individual patient data meta-analysis. Data sources We searched MEDLINE, EMBASE, Web of Science and Citation Index and Cochrane Register of Controlled Trials (CENTRAL<ext-link ext-link-type="unknown" id="intr0010" xlink:type="simple" xlink:href="http://www.cochrane.org/editorial-and-publishing-policy-resource/cochrane-central-register-controlled-trials-central" xmlns:xlink="http://www.w3.org/1999/xlink">http://www.cochrane.org/editorial-and-publishing-policy-resource/cochrane-central-register-controlled-trials-central) for relevant papers. Data extraction and data synthesis We screened for randomised controlled trials with ≥500 or more participants, and cohort studies of ≥1000 or more participants. We examined all publications related to these studies for any reported moderator analyses. Two reviewers independently did risk of bias assessment of main results and quality assessment of any moderator analyses. Results We included four randomised trials (n = 7208). Potential moderators with strong evidence (p < 0.05) in one or more studies were age, employment status and type, back pain status, narcotic medication use, treatment expectations and education. Potential moderators with weaker evidence (0.05 < p ≤ 0.20) included gender, psychological distress, pain/disability and quality of life. Conclusion There are insufficient robust data on moderators to be useful in clinical practice. This review has identified some important potential moderators of treatment effect worthy of testing in future confirmatory analyses.